The psychoanalytic symptom: clinic and culture - Aceituno M., Roberto (Revista de Psicología, 2001)
The article discusses the discoursive historicity of the psychiatric and psychoanalytic disciplines from two standpoints: the first, refers to the history of psychiatric and psychoanalytic discours; the second, refers to the "present" of psychiatric and psychoanalytic kwnowledge, in its relation to the problem analyzed before. The place of "borderlines" is analyzed specifically, considered as an expresion of both a disciplinary constancy and contemporary subjectivity in its social-cultural dimension.